Strategi Komunikasi Polda Kepulauan Riau Dalam Menjaga Citra Positif Instansi - Abdurrafi, Ammar; Cindoswari, Ageng Rara (Communicology: Jurnal Ilmu Komunikasi, 2023)
ABSTRACT Not many people realize the importance of having a positive image for individuals, companies, organizations and institutions, both government and non-government. Because other people's judgments and views of us or the organization we are in depend on the image we have. Police agencies are no exception, police agencies at the central and regional levels also expect a positive image, this affects the level of public trust in these institutions. Based on research that was previously found, the Riau Islands Regional Police, including agencies that have a positive image, in 2019 the level of public trust in the Police through 34 Regional Police has a value of 77.36%. This study aims to explore the communication strategy of the Riau Islands Police in maintaining the positive image of the institution, this research was carried out using descriptive qualitative research methods, the respondents in this study were 6 people, the key informants in this study were members of the Riau Islands Police Public Relations Division, as for other supporting informants are journalists, stakeholders, and society. The data in this study were analyzed using the credibility test, transferability test, dependability test and confirmability. The results of this study are that the Riau Islands Police have 3 main strategies in maintaining the positive image of the institution, the first is the general strategy, which is the strategy carried out by public relations like Media Relations, CSR, Campaign, after that the seccond the applied strategy is implementing the strategy from the center, then the follow-up strategy is strengthening member performance. The three strategies are mutually sustainable in the institution's efforts to maintain a positive image. Keyword : CSR; Communication Strategy; Positive Image; Media Relations ABSTRAK Tidak banyak orang yang menyadari pentingnya memiliki citra positif bagi individu, perusahaan, organisasi dan institusi, baik pemerintah maupun non-pemerintah. Karena penilaian dan pandangan orang lain terhadap kita atau organisasi tempat kita bernaung bergantung pada citra yang kita miliki. Tidak terkecuali instansi kepolisian, instansi kepolisian di tingkat pusat maupun daerah juga mengharapkan citra yang positif, hal ini berpengaruh pada tingkat kepercayaan masyarakat terhadap instansi tersebut. Berdasarkan penelitian yang telah ditemukan sebelumnya, Polda Kepulauan Riau termasuk instansi yang memiliki citra positif, pada tahun 2019 tingkat kepercayaan masyarakat terhadap Polri melalui 34 Polda memiliki nilai 77,36%. Penelitian ini bertujuan untuk mengeksplorasi strategi komunikasi Polda Kepulauan Riau dalam mempertahankan citra positif institusi, penelitian ini dilakukan dengan menggunakan metode penelitian kualitatif deskriptif, responden dalam penelitian ini berjumlah 6 orang, informan kunci dalam penelitian ini adalah anggota Bidang Humas Polda Kepri, adapun informan pendukung lainnya adalah jurnalis, stakeholder, dan masyarakat. Data dalam penelitian ini dianalisis dengan menggunakan uji kredibilitas, uji transferabilitas, uji dependabilitas dan konfirmabilitas. Hasil dari penelitian ini adalah Polda Kepri memiliki 3 strategi utama dalam mempertahankan citra positif institusi, yang pertama adalah strategi umum yaitu strategi yang dilakukan oleh humas seperti Media Relations, CSR, Kampanye, setelah itu yang kedua strategi terapan yaitu menerapkan strategi dari pusat, kemudian strategi lanjutan yaitu penguatan kinerja anggota. Ketiga strategi tersebut saling berkesinambungan dalam upaya lembaga mempertahankan citra positif. Kata Kunci : CSR; Citra Positif; Media Relations; Strategi Komunikasi